Audio-visual interaction in perception of industrial plants – Effects of sound level and the degree of visual masking by vegetation. (March 2020) - Haapakangas, Annu; Hongisto, Valtteri; Oliva, David
Abstract: Auditory and visual information interact in the perception of an environment and its sounds. While these phenomena may have implications for noise abatement, there has been little research on the role of the degree of sound source visibility when using vegetation as a visual and auditory shield. This laboratory experiment manipulated the level of vegetation masking an image of an industrial plant (0%, 30%, 60%, and 90% masking) and the sound level of industrial noise (40, 45, 55, 65, and 75 dB L Aeq ), and tested their effects and interaction on the perceived pleasantness of scenery and noise annoyance. An 11-point scale was used for both ratings. A repeated-measures design was applied where all thirty participants rated all combinations of images and sound levels. Contrary to expectations, the degree of visual masking did not affect noise annoyance. However, an interaction between sound level and visual masking was observed for the pleasantness of scenery, indicating that the effects of visual masking decreased with increasing sound level. The study contributes to the literature on sound source visibility and the role of vegetation in audio-visual perception of environmental noise sources and demonstrates the need to further investigate these issues.